Model Pengembangan Manajemen Ekonomi Pesantren pada Unit-Unit Usaha di Pondok Pesantren Salaf Modern Thohir Yasin - Nasrullah, Nasrullah; Aziz, Ahmad Amir; Badriati, Baiq El; Amini, Titik Husnawati (Universitas Hamzanwadi, 2024)
The economic development of Islamic boarding schools through business units is an additional activity besides teaching and learning to support the operational costs of Islamic boarding schools. The purpose of this research is to find out the economic management development model of PPSM Tohir Yasin and its implications for the boarding school, alumni, administrators and the surrounding community. This research uses a qualitative approach by conducting in-depth interviews, observation, documentation, to get significant results, the interview process involves the board of CV. Tohir Yasin consists of the Director, Brand Manager and Employees of the business units. The results of this study explain that there are two economic management development models used, namely First, the holding model is a management system that combines all business units into one to facilitate the acceleration of business achievements, financial administration using the digital-based SIDIK (Collective Digital Information System) application system, vision and mission of building a cottage. The two service models are systems that are accepted to empower alumni in managing existing business units such as the business unit sector, agriculture, plantations, fisheries, animal husbandry, health, services without being paid but given honorarium from business income. Then the implication of the development of business units on the boarding school is that the alumnus is not a member of the boarding school.